Revisión taxonómica del género Mimosa (Leguminosae-Mimisoideae) en el estado de Guerrero, México - López Mendoza, Alejandra (Universidad Autónoma Metropolitana, 2018)
Mimosa L. comprises ca. 540 species in the world; in Mexico, 105 species (ca. 20% of the genus) are found; according to previous registers to this thesis, the most diverse states in species of Mimosa have been: Oaxaca (46), Chiapas (35), and Veracruz (26). Diverse taxonomic studies of Mimosa have been performed at the regional level, including the states of Nayarit, Jalisco, Colima, Michoacán, Aguascalientes, Guanajuato, Querétaro, Nuevo León, Veracruz, Tlaxcala, Puebla, Morelos, Oaxaca, Tabasco, Chiapas, Campeche, Yucatán, and Quintana Roo; the present research contributes to the knowledge of the genus in Mexico, due to the fact that its taxonomic revision in Guerrero had not been undertaken up to date. Therefore, the goal of this thesis was to perform a taxonomic study of the diversity and distribution of the genus Mimosa in the state of Guerrero, Mexico. The revision of taxonomic and floristic literature was made, and the specimens of Mimosa collected in Guerrero and deposited in the herbarium of Facultad de Ciencias (FCME), UNAM, herbarium of Centro Regional del Bajío (IEB), Pátzcuaro, INECOL, Herbario Nacional (MEXU) Instituto de Biología, UNAM, and Herbario Metropolitano (UAMIZ), UAM-Iztapalapa, were examined. Main results show that 44 species of Mimosa occur in Guerrero, placing the state as the second one after Oaxaca; this corresponds to 42% out of the total of species of the genus in Mexico. Mimosa is also diverse in habit, including herbs and subshrubs, shrubs and trees, vines and lianes, as well as in the type of inflorescence and type of fruit. All this diversity is reflected in the representation of most sections (four), a high number of series (16) and of three subseries of the genus in Guerrero. Section Batocaulon is the best represented with the highest species number (25) while sect. Mimadenia has only one species in the state. In the taxonomic treatment, several cases of lectotypification were found, such as those of Mimosa affinis B.L. Rob., M. caerulea Rose, and M. egregia Sandwith. A key to the species and descriptions of species and varieties are presented. Respect to phenology, the flowering period of most species of Mimosa in Guerrero comprises from June to November and the fruiting period occurs from August to December. Distribution maps of the species occurring in the three floristic provinces that converge in the state are presented: i) Balsas Basin, ii) Meridional Mountain ranges, and iii) Pacific Coast. The most diverse floristic province is that of Meridional Mountain ranges (31 spp.), followed by the Balsas Basin (26 spp.) and by the Pacific Coast (24 spp.). It is important to point out that a taxon can be distributed in two or three provinces, as Mimosa albida Humb. & Bonpl. ex Willd. var. glabrior B.L. Rob., M. camporum Benth., M. pigra L. var. pigra, M. polyantha Benth. and M. tricephala Schltdl. & Cham. var. nelsonii (B.L. Rob.) Chehaibar & R. Grether. Some other taxa are found only in one province, such as Mimosa sotoi R. Grether & V.W. Steinm., M. caerulea Rose, M. distachya Cav., M. grahamii A. Gray var. grahamii, M. psilocarpa B.L. Rob., M. sicyocarpa B.L. Rob., M. tarda Barneby, and M. watsonii B.L. Rob. In Guerrero, there are several species endemic to Mexico, and these are narrow endemics with restricted distribution and other have a wide distribution in the country. Mimosa is found along a wide altitudinal range, from sea level to 2800 m. During development of this thesis, new registers of 14 taxa for the state were found, which widens their distribution area to Guerrero; in some cases, it is the northern limit (ex. Mimosa polydactyla Humb. & Bonpl. ex Willd.) and in other, the southern limit (ex. Mimosa grahamii var. grahamii). It is important to point out that additional field work is still necessary in diverse zones of the state, due to the scarce material of some species of Mimosa in the consulted herbaria, specially of those species not previously registered in the state. Furthermore, there are very antique collections and it would be important to make new explorations to update the geographic distribution and to determine if some invasive species have widened their distribution, if the distribution area has been reduced or if the species are still in the same localities; Mimosa L. comprende ca. 540 especies a nivel mundial, en México se encuentran 105 (ca. 20% del género); con base en registros previos a esta tesis, los estados más diversos en especies de Mimosa han sido: Oaxaca (46), Chiapas (35) y Veracruz (26). Se han realizado diversos estudios taxonómicos de Mimosa a nivel regional, incluyendo los estados de Nayarit, Jalisco, Colima, Michoacán, Aguascalientes, Guanajuato, Querétaro, Nuevo León, Veracruz, Tlaxcala, Puebla, Morelos, Oaxaca, Tabasco, Chiapas, Campeche, Yucatán y Quintana Roo; el presente trabajo contribuye al conocimiento del género en México, ya que hasta ahora, no se había llevado a cabo su revisión taxonómica en Guerrero. Por lo anterior, el objetivo de este trabajo fue realizar un estudio taxonómico, de la diversidad y distribución del género Mimosa en el estado de Guerrero, México. Se hizo la revisión de literatura taxonómica y florística y se examinaron los ejemplares del género recolectados en Guerrero y depositados en los herbarios de la Facultad de Ciencias (FCME), UNAM, del Centro Regional del Bajío (IEB), Pátzcuaro, INECOL, del Herbario Nacional (MEXU) Instituto de Biología, UNAM y del Herbario Metropolitano (UAMIZ), UAM-Iztapalapa. Los principales resultados muestran que 44 especies de Mimosa crecen en Guerrero, ubicando al estado en el segundo lugar, después de Oaxaca; esto representa el 42% del total de especies del género en México. Mimosa también es diverso en formas biológicas, desde hierbas y sufrútices, arbustos y árboles hasta trepadoras y lianas, así como en el tipo de inflorescencia y tipo de legumbre, lo que se refleja en la representación de la mayoría de las secciones (cuatro), de un alto número de series (16) y de tres subseries del género en el estado. La sección Batocaulon es la mejor representada, con el mayor número de especies (25) y la sección Mimadenia es la que cuenta sólo con una especie. En cuanto a la fenología, el período de floración de la mayoría de las especies de Mimosa en Guerrero comprende los meses de junio a noviembre y el período de fructificación ocurre en los meses de septiembre a diciembre. En el tratamiento taxonómico se encontraron casos de lectotipificación, como los de Mimosa affinis B.L. Rob., M. caerulea Rose y M. egregia Sandwith. Asimismo, se elaboró una clave de identificación y la descripción de las especies y variedades del género. Respecto a la fenología, el período de floración de la mayoría de las especies de Mimosa en Guerrero comprende los meses de junio a noviembre y el período de fructificación ocurre en los meses de agosto a diciembre. Se presentan mapas de distribución de las especies registradas en las tres provincias florísticas que convergen en el estado: i) Depresión del Balsas, ii) Serranías Meridionales y iii) Costa Pacífica. La provincia florística más diversa es la de las Serranías Meridionales (31 spp.), seguida de la Depresión del Balsas (26 spp.) y de la Costa Pacífica (24 spp.). Cabe resaltar que un taxon se puede distribuir en dos o en las tres provincias, como Mimosa albida Humb. & Bonpl. ex Willd. var. glabrior B.L. Rob., M. camporum Benth., M. pigra L. var. pigra, M. polyantha Benth. y M. tricephala Schltdl. & Cham. var. nelsonii (B.L. Rob.) Chehaibar & R. Grether. También hay otros taxa que se encuentran en una sola provincia, como Mimosa sotoi R. Grether & V.W. Steinm., M. caerulea Rose, M. distachya Cav., M. grahamii A. Gray var. grahamii, M. psilocarpa B.L. Rob., M. sicyocarpa B.L. Rob., M. tarda Barneby y M. watsonii B.L. Rob. En Guerrero, existen varias especies que son endémicas de México y éstas tienen distribución restringida o pueden tener una amplia distribución dentro del país. Mimosa tiene una distribución en el estado con un intervalo altitudinal que va desde el nivel del mar hasta los 2800 m. Durante la elaboración de este trabajo, se encontraron registros nuevos de 14 taxa para el estado, lo que amplía su área de distribución a Guerrero, siendo el límite norte de algunas (p. ej. Mimosa polydactyla Humb. & Bonpl. ex Willd.) o el límite sur de otras (p. ej. Mimosa grahamii var. grahamii). Es necesario realizar trabajo de campo adicional en diversas zonas del estado, ya que se encuentra poco material de algunas especies de Mimosa en los herbarios consultados, en particular de aquellas que no se habían registrado previamente en el estado. También existen colectas que son muy antiguas y sería importante realizar nuevas exploraciones para actualizar la distribución geográfica y determinar si algunas especies invasoras ampliaron su distribución, si su área de distribución se ha reducido o si aún permanecen en las mismas localidades